Pengaruh Variabel Makro Terhadap Pembiayaan Rahn pada Perbankan Syariah - Asma Rita; Ahmad Ajib Ridlwan (Journal Of Institution And Sharia Finance, 2023)
This study uses secondary data sources that was taken from BI and BSI. Numerical data obtained from secondary data ware analyzed using multiple linear regression along with other prerequisite statistical tools. Basen and the results of hypothesis testing, it can be concluded that the inflation rate variable (X1), bi rate (X2) and gold price (X4) has a negative and significant influence on rahn financing (Y), while the variable exchange rate (X3) had positive and significant rahn financing (Y). in addition, the coefficient of determinasi (adjested R square) of the macro variable on rahn’s financing obtained a value of 0,822 or 82% which means the rahn’s financing can be explained by macro variable of 82%, the remaining 17,8% is explained by other variables outside the research, such as the number of customers, the amount of money in circulation and the income of the mortgage.